2002
DOI: 10.1086/342316
|View full text |Cite
|
Sign up to set email alerts
|

Physical Structure of the Proto–Planetary Nebula CRL 618. I. Optical Long‐Slit Spectroscopy and Imaging

Abstract: In this paper we present optical long-slit spectroscopy and imaging of the proto-planetary nebula CRL 618. The optical lobes of CRL 618 consist of shock-excited gas, which emits many recombination and forbidden lines, and dust, which scatters light from the innermost regions. From the analysis of the scattered H emission, we derive a nebular inclination of i ¼ 24 AE 6 . The spectrum of the innermost part of the east lobe (visible as a bright, compact nebulosity close to the star in the H Hubble Space Telescope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Our interpretation is also consistent with the fact that most PPNs exhibit intrinsic polarization of the continuum as well as some emission lines, which are most likely due to scattering off dust grains (Trammell et al 1994). In particular, Balmer lines seem to come from an H ii region close to the star, which is blocked from direct view by, e.g.,the thick equatorial dust waists commonly present in these objects, and are seen in reflection off the nebular dust (see also, e.g., Sánchez Contreras et al 2002).…”
Section: Correlationsmentioning
confidence: 97%
“…Our interpretation is also consistent with the fact that most PPNs exhibit intrinsic polarization of the continuum as well as some emission lines, which are most likely due to scattering off dust grains (Trammell et al 1994). In particular, Balmer lines seem to come from an H ii region close to the star, which is blocked from direct view by, e.g.,the thick equatorial dust waists commonly present in these objects, and are seen in reflection off the nebular dust (see also, e.g., Sánchez Contreras et al 2002).…”
Section: Correlationsmentioning
confidence: 97%
“…For example, CRL 2688, the Egg Nebula, exhibits both low (Ͻ20 km⅐s Ϫ1 ) and high velocity (Ͼ100 km⅐s Ϫ1 ) outflows (24,25). A more evolved object is CRL 618; here, the star, which has lost its dusty shroud, is producing sufficient UV radiation to create a small, nearby HII region (26,27).…”
Section: The Chemical Environment Of Circumstellar Shellsmentioning
confidence: 99%
“…AFGL618, also named the Westbrook Nebula, is a young proto-PN (∼200 years Kwok & Bignell 1984) exhibiting a B0 central star, a central compact HII region (Sánchez Contreras et al 2002), and two pairs of rapidly expanding well collimated lobes (Balick et al 2013). SMA continuum and CO-line-polarisation observations of Sabin et al (2014) have revealed a magnetic field well aligned and organised along the polar direction, suggesting a magnetic-outflowlaunching mechanism.…”
Section: Source Samplementioning
confidence: 99%